The impact of the oral condition of children with sickle cell disease on family quality of life - Maria Luiza da Matta Felisberto FERNANDES; Ichiro KAWACHI; Patrícia CORRÊA-FARIA; Saul Martins PAIVA; Isabela Almeida PORDEUS (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to assess the impact of oral conditions of children with sickle cell disease (SCD) on their parents' quality of life (QoL). A cross-sectional study was performed with parents of outpatients suffering from SCD at a hematology referral center in Belo Horizonte, MG. A qualified dentist performed an intraoral exam. The Family Impact Scale (FIS) was used to assess the parents' perception of QoL. The parents answered some questions regarding sociodemographic and medical information about their children. The dmft/DMFT score, DAI, gum bleeding and SCD severity were evaluated in terms of their impacts on the overall mean FIS scores and subscale scores. The chance of more frequent impacts was greater in parents of adolescents (OR = 2.04; 95%CI = 1.2, 3.4) than of younger children. Dental caries (dmft/DMFT ≥ 1) had a negative impact on the QoL of parents of younger children and adolescents (p < 0.05 and p < 0.01, respectively). Among the parents of younger children, dental caries and SCD severity significantly affected the subscales for parental activities (PA) and parental emotions (PE) (p < 0.01, p < 0.05, respectively). Among parents of adolescents, dental caries (DMFT) and severe malocclusion adversely affected the PE and PA subscales (p < 0.01, p < 0.05, respectively). SCD severity affected the overall FIS score among young children's parents (p < 0.05). In conclusion, dental caries, age and SCD severity were associated with a negative impact on the QoL of parents of children with SCD